Gender Dynamics in the Agricultural Sector in the NTT-Timor Leste Border Region - Nalle, Frederic Winston; Seran, Sirilius; Klau, Anggelina Delviana (Jurnal Economia, 2025)
AbstractWomen play a crucial role in the agricultural sector in the NTT-Timor Leste border region but continue to face economic disparities. This study examines the impact of job type, education, resource access, socio-cultural norms, and health on the income of women farmers. Using simple random sampling and Slovin's formula, 100 respondents were selected from a population of 66,545 women farmers across four border districts. Multiple linear regression analysis indicates these factors significantly influence women farmers' income. The findings highlight the need to improve access to agricultural resources, education, and healthcare services to support women's economic empowerment and reduce economic disparities in border areas.